Some results on boundary value problems for functional differential equations - P. Ch. Tsamatos; S. K. Ntouyas (International Journal of Mathematics and Mathematical Sciences)
Existence results for a second order boundary value problem for functional differential equation, are givn. The results are based on the nonlinear Alternative, of Leray-Schauder and rely on a priori bounds on solutions. These results are generalizations of recent results from ordinary differential equations and complete our earlier results on the same problem.